Smithfield CARES (Community Accessing Resources, Education, and Screenings) Primary Care Clinic - Hinnant, Margaret (My University, 2018)
The Smithfield CARES Primary Care Clinic DNP Project was a quality improvement project to develop a primary care clinic at the Smithfield Rescue Mission, a homeless shelter, in Johnston County. Research indicates that homeless populations have poorer health outcomes than the rest of the population. The purpose of the on-site primary care clinic is to provide health care to homeless persons in a cost-effective manner while decreasing barriers to care. Using Jean Watson’s Theory of Human Caring as a foundation, a once- a- week clinic was developed at the Smithfield Rescue Mission. The clinic addressed the health needs of the Smithfield Rescue Mission residents and connected them with appropriate community resources. The design of the clinic can easily be implemented at other homeless shelters.
Keywords: Primary Care Clinic; Homeless